2019
DOI: 10.1016/j.applthermaleng.2019.02.035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of working fluid properties on the performance of a miniature free piston expander for waste heat harvesting

Abstract: Power generation from waste heat sources at the miniature length scales may be generated by using phase change working fluids (liquid-to-vapor) in a traditional boiler-expander-condenser-pump system. This paper builds on our prior work of boiler and expander design by investigating the effects of working fluid properties on an expander unit based on a Free Piston (FPE) architecture. Here, using first principles, a lumped-parameter model of the FPE is derived by idealizing the FPE as a linear spring-mass-damper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Because of low efficiencies in the MEMS scale, an open-cycle macro-scale FP-LEG was developed. 62,63 The intake duration and pressure influenced the performance indicators, similar to the result by Jia et al 26 An indicated efficiency of 18% at 2.5 bar, 373 K, was achieved. 62 Increased intake temperature did not significantly affect engine performance for a fixed intake duration, and an optimal intake duration existed, which maximised energy conversion, similar to the results in Ngwaka et al 64…”
Section: Linear Engine Developmentssupporting
confidence: 78%
“…Because of low efficiencies in the MEMS scale, an open-cycle macro-scale FP-LEG was developed. 62,63 The intake duration and pressure influenced the performance indicators, similar to the result by Jia et al 26 An indicated efficiency of 18% at 2.5 bar, 373 K, was achieved. 62 Increased intake temperature did not significantly affect engine performance for a fixed intake duration, and an optimal intake duration existed, which maximised energy conversion, similar to the results in Ngwaka et al 64…”
Section: Linear Engine Developmentssupporting
confidence: 78%
“…Commonly, the presence of simplified prototypes and/or different working conditions could determine several differences between the actual machine performance and the measured ones. To help the experimental analysis, a lumped-parameter model is often used for extending the analysis to other operating conditions or other fluids [7,8], increasing the design capabilities and limiting the cost and time.…”
Section: Introductionmentioning
confidence: 99%
“…Burugupally et al indirectly studied the influence of viscous friction on the performance of FPE during operation by studying the different performance of FPE with different viscosity working fluid. However, this paper only analyzed the performance influence, and did not make a detailed analysis on the power consumption and magnitude of viscous friction [22].…”
Section: Introductionmentioning
confidence: 99%